IMAGIN(G) HERITAGE (diségno, 2023)
The fourth biennial meeting of the conferences organized by IMG-Network was held at the University of L’Aquila, on July 6th and 7th, 2023, under the direction of Stefano Brusaporci. The theme chosen for this edition of the International and Interdisciplinary Conference on Image and Imagination was dedicated to IMAGIN(G) HERITAGE, a context that combines two very broad fields of research –those of Heritage and Images related to it– in the plurality of variations that this relationship can encompass. [read more]